Common influences, spillover and integration in Chinese stock markets - Enzo Weber; Yanqun Zhang (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
The Chinese stock market features an interesting history of divided market segments: domestic (A), foreigners' (B) and overseas (H). This puts forth questions of market integration as well as cross-divisional information transmission. We address these issues in a structural DCC framework, an econometric technique capable of identifying common factor in uences from (bi-directional) spillovers as constituents of contemporaneous correlations. We find initial dominance of transmission from A to B and to a lesser extent from H to B and A to H. However, since the opening of the B-market for Chinese citizens in 2001, common factors have largely replaced direct spillovers.
Keywords: C32; G10; 330; China; stock market; integration; causality; correlation; Aktienmarkt; Marktsegmentierung; Börsenkurs; Spillover-Effekt; Kausalanalyse; Korrelation; China